Menumbuhkan Kepercayaan Diri pada siswa di MAN 2 Surakarta - Aqvina Rahma Diyanti; Faqih Purnomosidi (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
A teenager is a person who grows up which includes mental, emotional, social, and physical maturity. Adolescence is a period that every individual always goes through. One of them is hugh school students, high school students have an age range of 15 to 18 years. Lack of self-confidence is one of the factors of problems experienced by students. The method used in this activity are (1) preparation stage, (2) implementation stage, and (3) evaluation stage. The subjects of this activity were students in class X and XI at Man 2 Surakarta. The aim of this activity is to grow students’ self-confidence. The result obtained are that students understand more and increase their self-confidence. In conclusion, self-confidence is important for students and more and more students are confident and confident in themselves.